Obtention of Enzymatically Hydrolyzed Product from Cactus (Opuntia boldinghii Britton and Rose) Cladodes Whole Flour - Pereira, C.A. Padron; Alvarez, M.J. Moreno; Martinez, C.A. Medina; Pantaleon, D.M. Garcia (Pakistan Journal of Nutrition, 2009)
The objective of this work was to obtain an enzymatically hydrolyzed product from cactus cladodes whole flour (Opuntia boldinghii Britton and Rose). The whole flour was subjected to the action of the commercially prepared enzymes Pectinex® Ultra SP-L and Cellubrix® L (1:1 ratio). The experiments were carried out under fixed conditions of temperature of 50oC ± 1oC and with pH of 5.5±0.1 under continuous agitation at 150 rpm. The kinetic parameters: enzyme and substrate optimal concentration, reaction time, KM, Vmax and K3 were established. It was observed that the fibrous constituents in the hydrolized flour decreased (P